RASIO SARI WORTEL DAN SARI BUAH NANAS TERHADAP KUALITAS PERMEN JELLY - Dewi, Seprina Putri; Harun, Noviar; Johan, Vonny Setiaries (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The purpose of this study was to get the right ratio of carrot extracts and pineapple extracts to produce jelly candy with good quality according to SNI. This research used a Complete Randomized Design (CRD) with five treatments and three replications to obtain fifteen experimental units. The treatment in this study included WN1 (carrot extracts 90% : 10% pineapple extracts), WN2 (carrot extracts 80% : 20% pineapple extracts), WN3 (carrot extracts 70% : 30% pineapple extracts), WN4 (Carrot extracts 60% : 40% pineapple extracts) and WN5 (carrot extracts 50% : 50% pineapple extracts). Data were analized using analysis of variance (ANOVA) then proceed with DNMRT test at 5% level. The results showed that the ratio of carrot extracts and pineapple extracts had significant effect on moisture content, ash content, pectin content, reduction sugar content, color, aroma, taste, texture and overall assessment of the jelly candy produced. The selected treatments that complied with SNI 3574-2-2008 were WN1 with a ratio of 90% carrot extracts and 10% pineapple extracts. The jelly candy produced contains 7.22% of moisture content, 0.82% of ash content, 2.29% of pectin content, 19.24% of reduction sugar content with description very orange (colour), carrot and pineapple (aroma), carrot and pineapple (taste) and slightly chewy (texture) and overall considered liked by the panelist with a score of 1.89. Keywords: jellycandy, carrot extracts, pineapple extracts.